2012
DOI: 10.2478/v10172-012-0035-2
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Tests of Steel Filtering Process

Abstract: The concerned paper presents results of wide scope of liquid steel filtering tests by means of ceramic filters, including laboratory, model and industrial testing in the conditions of conventional (ingot) and continuous steel casting. Multi-hole (sieve) ceramic filters made of mullite and corundum, of the structure adjusted to the type of conducted experiment were used for testing. Selection of ceramic material for filter construction accounted for the conditions of filter operations including: high temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In the technical bibliography [22][23][24][25][26] the authors analyse a very similar topic but they deal with different quality types of steel, and the chemical composition of the non-metallic inclusions differs as well, nevertheless the basic principle is the same. In the given specific literature, the authors underlined the increase of the non-metallic inclusions content that occurred after the increase of the steel cast speed Fig.6.…”
Section: Fig 2 Graphical Dependency Between the Present Non-metallicmentioning
confidence: 99%
“…In the technical bibliography [22][23][24][25][26] the authors analyse a very similar topic but they deal with different quality types of steel, and the chemical composition of the non-metallic inclusions differs as well, nevertheless the basic principle is the same. In the given specific literature, the authors underlined the increase of the non-metallic inclusions content that occurred after the increase of the steel cast speed Fig.6.…”
Section: Fig 2 Graphical Dependency Between the Present Non-metallicmentioning
confidence: 99%
“…[28,29] Industrial tests indicated that ceramic filters could effectively remove small inclusions in steel by absorbing inclusions. [30,31] Furthermore, ceramic filters can improve the flow conditions of liquid steel, and promote the floating and removal of inclusions in steel. [32] Recently, the microporous magnesia was also applied in ceramic filters and exhibited excellent mechanical properties, thermal shock resistance, and filtration efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of information technology, many methods such as filtering [27,28], estimation [29,30], and online detection [31,32] for industrial processes have been proposed, and most of them involve the soft sensing technology.…”
Section: Introductionmentioning
confidence: 99%